Geological nonhomogeneity of soils - Kaczyński, R.; Bąkowska, A. (Інститут прикладних проблем механіки і математики ім. Я.С. Підстригача НАН України, 2008)
The nonhomogeneity of typical soils in Poland (Tertiary, Miocene and Pliocene clays, Quaternary glacial tills and loesses, Holocene fluvial sands) was analyzed in the paper. The analysis was limited to the presentation of the results of investigation of variability coefficient V and Kagan nonhomogeneity coefficient K1 determined for the basic parameters of lithological, microstructural, physical and mechanical properties used for designing the foundations of engineering objects. Nonhomogeneity of soils is determined by the geological conditions of their origin as well as by later changes.